Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Navigating Civic Space in a Time of COVID-19: The Case of Mozambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Institute for Social and Economic Studies, 2021)
This report builds on the Action for Empowerment and Accountability (A4EA) research project Navigating Civic Space, which seeks to analyze the extent to which COVID-19 is contributing to the opening or closing of space for civic action in three countries, namely Mozambique, Nigeria and Pakistan. Focusing on Mozambique, the report uses theoretical and methodological tools produced by the work stream and is essentially structured around the three main research questions: What is known about the civic space trend in Mozambique before the arrival of the COVID-19 pandemic?; How are different actors responding to the COVID-19 pandemic affecting the civic space in Mozambique?; What are the medium and long term implications for governance in Mozambique?
Accepted: 2021-04-28T09:57:56Z
Keywords: G - Mozambique / Moçambique; L - english / inglês; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Publisher: African Development Bank Group 978-9973-9854-5-3 (electronic)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Publisher: Centro Brasileiro de Análise e Planejamento
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Sixth Invertors Group Meeting
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

Health provider responsiveness to social accountability initiatives in low- and middle-income countries: a realist review - Lodenstein, Elsbet; Dieleman, Marjolein; Gerretsen, Barend; Broerse, Jacqueline E W (Health Policy and Planning, 2017)
Social accountability in the health sector has been promoted as a strategy to improve the quality and performance of health providers in low- and middle-income countries. Whether improvements occur, however, depends on the willingness and ability of health providers to respond to societal pressure for better care. This article uses a realist approach to review cases of collective citizen action and advocacy with the aim to identify key mechanisms of provider responsiveness. Purposeful searches for cases were combined with a systematic search in four databases. To be included in the review, the initiatives needed to describe at least one outcome at the level of frontline service provision. Some 37 social accountability initiatives in 15 countries met these criteria. Using a realist approach, retroductive analysis and triangulation of methods and sources were performed to construct Context–Mechanism–Outcome configurations that explain potential pathways to provider responsiveness. The findings suggest that health provider receptivity to citizens’ demands for better health care is mediated by health providers’ perceptions of the legitimacy of citizen groups and by the extent to which citizen groups provide personal and professional support to health providers. Some citizen groups activated political or formal bureaucratic accountability channels but the effect on provider responsiveness of such strategies was more mixed. Favourable contexts for health provider responsiveness comprise socio-political contexts in which providers self-identify as activists, health system contexts in which health providers depend on citizens’ expertise and capacities, and health system contexts where providers have the self-perceived ability to change the system in which they operate. Rather than providing recipes for successful social accountability initiatives, the synthesis proposes a programme theory that can support reflections on the theories of change underpinning social accountability initiatives and interventions to improve the quality of primary health care in different settings.
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde

Effects of food price shocks on child malnutrition: The Mozambican experience 2008/2009 - Arndt, Channing; Hussain, M. Azhar; Salvucci, Vincenzo; Østerdal, Lars Peter (Elsevier, 2016)
A propitiously timed household survey carried out in Mozambique over the period 2008/ 2009 permits us to study the relationship between shifts in food prices and child nutrition status in a low income setting. We focus on weight-for-height and weight-for-age in different survey quarters characterized by very different food price inflation rates. Using propensity score matching techniques, we find that these nutrition measures, which are sensitive in the short run, improve significantly in the fourth quarter of the survey, when the inflation rate for basic food products is low, compared to the first semester or three quarters, when food price inflation was generally high. The prevalence of underweight, in particular, falls by about 40 percent. We conclude that the best available evidence points to food penury, driven by the food and fuel price crisis combined with a short agricultural production year, as substantially increasing malnutrition amongst under-five children in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde; ⛔ No DOI found

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

Effects of food price shocks on child malnutrition: the Mozambican experience 2008/09 - Arndt, Channing; Hussain, M. Azhar; Østerdal, Lars Peter (World Institute for Development Economics Research (WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Journal Abbreviation: tThe Group Effect: Social Cohesion and Health Outcomes Pages: 171 Publication Title: tThe Group Effect: Social Cohesion and Health Outcomes
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água; higiene e saneamento; health / saúde; private sector / setor privado

Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Northwestern University's Program of African Studies, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Publisher: Wiley Online Library
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Accepted: 2016-02-01T14:49:31Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde